Pengaruh Pertimbangan Pasar Kerja, Penghargaan Finansial Dan Pengakuan Profesional Terhadap Minat Mahasiswa Jurusan Akuntansi Untuk Berkarir Sebagai Konsultan Pajak: (Studi Kasus Mahasiswa Program Studi Akuntansi Universitas Hindu Indonesia) - Riski Anggreni, Ni Wayan; Hutnaleontina, Putu Nuniek; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2025)
The interest of students majoring in accounting in pursuing a career as a tax consultant must be considered in order to provide professional tax consultant workers who have an important role in helping taxpayers to accompany and assist the public in carrying out their tax obligations. This research to investigate the impact of job market factors, financial incentives, and professional acknowledgment on the inclination of accounting students to opt for a career as tax consultants. The research targeted all accounting students at the Indonesian Hindu University, with a sample comprising 8th-semester students who had completed the comprehensive taxation course, totaling 176 individuals. Purposive sampling was employed as the sampling method. The data underwent validity, reliability, multicollinearity, and heteroscedasticity tests, followed by multiple linear regression analysis, hypothesis testing, and determination coefficient assessment. The results show that the variables of job market considerations, financial rewards, and professional recognition have a positive and significant effect on the interest of students majoring in accounting in a career as a tax consultant for students of the Indonesian Hindu University accounting study program.